2017
DOI: 10.1016/j.bbamem.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Magic angle spinning 31P NMR spectroscopy reveals two essentially identical ionization states for the cardiolipin phosphates in phospholipid liposomes

Abstract: Specific membrane lipid composition is crucial for optimized structural and functional organization of biological membranes. Cardiolipin is a unique phospholipid and important component of the inner mitochondrial membrane. It is involved in energy metabolism, inner mitochondrial membrane transport, regulation of multiple metabolic reactions and apoptotic cell death. The physico-chemical properties of cardiolipin have been studied extensively but despite all these efforts there is still lingering controversy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…While the pKa of the phosphates of CL had originally been described as strong acids and were doubly negatively charged [53], a pH titration study comparing a native and 2'-deoxy-glycerol backbone suggested that there was both a low and high pKa[54]. Subsequently membrane measurements of CL using external proton adsorption, electrophoretic mobility of membranes and magic angle spinning P 31 NMR have clearly shown that the pKa of CL as well as lyso-CL is ~2-3 indicating that both phosphates are ionized at physiological pH in lipid bilayers [55-57]. Thus it seems logical or almost certain that at physiological pH, CLs in lipid bilayers adopt the states with two fully ionized phosphate groups.…”
Section: Cardiolipin Its Molecular Structure Homo- and Hetero-acylamentioning
confidence: 99%
“…While the pKa of the phosphates of CL had originally been described as strong acids and were doubly negatively charged [53], a pH titration study comparing a native and 2'-deoxy-glycerol backbone suggested that there was both a low and high pKa[54]. Subsequently membrane measurements of CL using external proton adsorption, electrophoretic mobility of membranes and magic angle spinning P 31 NMR have clearly shown that the pKa of CL as well as lyso-CL is ~2-3 indicating that both phosphates are ionized at physiological pH in lipid bilayers [55-57]. Thus it seems logical or almost certain that at physiological pH, CLs in lipid bilayers adopt the states with two fully ionized phosphate groups.…”
Section: Cardiolipin Its Molecular Structure Homo- and Hetero-acylamentioning
confidence: 99%
“…The ionization state of the two phosphate moieties of CL has been a debated topic. Recent studies suggest that CL is doubly deprotonated at physiological pH and carries a charge of À2 (9)(10)(11)(12), though other literature indicates circumstances in which CL can carry a À1 charge (13)(14)(15)(16). The tuning of CL's charge state will affect the headgroup charge repulsion and modulate molecular geometry.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Despite concurrent work which supported protonation of a CL phosphate in this pH regime, 25 recent studies question whether a CL phosphate ionizes near physiological pH. 26,27 Furthermore, the reverse micelle study, which identified site N, did not detect evidence for a CL binding site near Asn52. 14 Discrepancies in the magnitudes of binding constants for sites A and C also exist in the literature.…”
Section: Introductionmentioning
confidence: 99%